Implementation Article 5 Paragraph 1 of Regional Regulation Number 1 On 2018 Concerning Education Provision (Case Study of Homeless Children in Barabai Territory) - Siti Julaiha (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2023)
ABSTRACT This paper is motivated by the existence of a regional regulation that regulates the government's efforts in organizing education, where every individual aged seven to fifteen years is required to carry out basic education as stipulated in regional regulation number 1 of 2018 concerning education implementation article 5 paragraph 1 which reads "every regional citizen aged seven to fifteen years is required to attend basic education" then, with this regulation every citizen of the Hulu Sungai Tengah district should have received education. However, the facts in the field prove that there are still many homeless children who should be at school age to get the right to education instead they are in public places to think about how to survive. This study aims to determine the implementation of article 5 paragraph 1 of regional regulation number 1 of 2018 concerning the implementation of education specifically for homeless children and to find out what factors hinder the implementation. This research uses a juridical sociological approach, which discusses legal knowledge normatively empirically by making direct observations to the object where this research is carried out not only examining laws and regulations, but observing the reactions and interactions that occur when the norm system works in society, besides that this research is carried out so that it can be useful both theoretically and practically. The implementation of article 5 paragraph 1 of regional regulation number 1 of 2018 concerning the implementation of education has not been implemented optimally. This is evidenced by the indication that there are still many homeless children hanging around in public places such as red light intersections, pedestrian bridges, shopping centers and others at an age that is still allowed to get education which explains that the first mission of the education office in increasing the availability of broad and equitable access to education has not fully run smoothly with several factors including unknown guardians, mindset changes in children, living like nomads, and reasons as a last resort. Keywords: Implementation, Education, Homeless Children ABSTRAK Tulisan ini dilatarbelakangi oleh adanya peraturan daerah yang mengatur tentang upaya pemerintah dalam menyelenggarakan pendidikan, dimana setiap individu yang berusia tujuh sampai dengan lima belas tahun wajib melaksanakan pendidikan dasar seperti yang tertuang dalam peraturan daerah nomor 1 tahun 2018 tentang penyelenggaraan pendidikan pasal 5 ayat 1 yang berbunyi "setiap warga daerah yang berusia tujuh sampai dengan lima belas tahun wajib mengikuti pendidikan dasar" maka dengan adanya peraturan tersebut seharusnya setiap warga negara kabupaten Hulu Sungai Tengah sudah mengenyam pendidikan. Namun, fakta di lapangan membuktikan bahwa masih banyak anak gelandangan yang seharusnya berada di usia sekolah untuk mendapatkan hak atas pendidikan justru berada di tempat umum untuk memikirkan bagaimana cara bertahan hidup. Penelitian ini bertujuan untuk mengetahui implementasi pasal 5 ayat 1 peraturan daerah nomor 1 tahun 2018 tentang penyelenggaraan pendidikan khusus anak gelandangan dan untuk mengetahui faktor-faktor apa saja yang menghambat implementasi tersebut. Penelitian ini menggunakan pendekatan yuridis sosiologis, yang membahas pengetahuan hukum secara normatif empiris dengan melakukan pengamatan langsung ke objek dimana penelitian ini dilakukan tidak hanya meneliti peraturan perundang-undangan, tetapi mengamati reaksi dan interaksi yang terjadi ketika sistem norma tersebut berjalan di masyarakat, selain itu penelitian ini dilakukan agar dapat bermanfaat baik secara teoritis maupun praktis. Implementasi pasal 5 ayat 1 peraturan daerah nomor 1 tahun 2018 tentang penyelenggaraan pendidikan belum terlaksana secara optimal. Hal ini dibuktikan dengan adanya indikasi masih banyaknya anak gelandangan yang berkeliaran di tempat umum seperti perempatan lampu merah, jembatan penyeberangan orang, pusat perbelanjaan dan lain-lain pada usia yang masih diperbolehkan untuk mendapatkan pendidikan yang menjelaskan bahwa misi pertama dinas pendidikan dalam meningkatkan ketersediaan akses pendidikan yang luas dan merata belum sepenuhnya berjalan dengan lancar dengan beberapa faktor antara lain tidak diketahui walinya, perubahan pola pikir pada anak, hidup merantau, dan alasan sebagai pilihan terakhir. Kata kunci: Implementasi, Pendidikan, Anak Tunawisma